Design of modern fine arts museum in Tondano - Fitri Fauziah Damayanti; Ferdinan S. R. P. Terok; Debbie Augustien Jeannet Harimu (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2023)
The design of the Museum of Modern Fine Arts is a place for artists to exhibit their works, because museums in North Sulawesi Province do not allow them to accept collections of modern art due to differences in museum classification, and there is no museum with the classification of art museums in North Sulawesi Province. The design theme for this design is Expressionism Architecture with the concept of Focus On Material. This design makes those who previously did not understand and have no interest in fine art develop a curiosity about something that is seen and become an attraction for the general public to visit. The design method used is the Five Step Design Process Method taken from the book